Phylogeography of Lanius senator in its breeding range: conflicts between alpha taxonomy, subspecies distribution and genetics. Issue 1 (31st December 2022) - Nasuelli, M.; Ilahiane, L.; Boano, G.; Cucco, M.; Galimberti, A.; Pavia, M.; Pioltelli, E.; Shafaeipour, A.; Voelker, G.; Pellegrino, I.
Abstract: Implementing efforts to understand biogeographic distribution patterns and taxonomic limits within animal groups is crucial for addressing several challenges of modern zoology. Although avian phylogeography has been extensively investigated within the Western Palearctic, several families, such as shrikes, still display unresolved or neglected biogeographic patterns both between and within species, thus requiring further investigations. The Woodchat Shrike ( Lanius senator ) is a long-distance migratory species that exhibits three morphologically well-recognizable subspecies, whose boundaries have never been phylogenetically investigated. Here, we aimed to define the phylogeographic structure of Lanius senator throughout its breeding range and assess the genetic coherence with respect to the phenotypically described subspecies. We assembled a collection of 34 samples mainly from breeding populations of each subspecies and analysed them using four mtDNA and two nuDNA markers. We did not find clear phylogenetic structure in nuclear Ornithine Decarboxylase (ODC) and Myoglobin intron 2 (MYO), but all the four mtDNA loci (i.e., ND2, COI, cytb and CR) highlighted two main haplogroups: one including both the nominate subspecies L. s. senator and L. s. badius and a second one consisting of L. s. niloticus (the easternmost part of its range). Surprisingly, individuals phenotypically assigned to L. s. niloticus from Israel were genetically assigned to the senator/badius haplogroup. Moreover, genetic distances between haplogroups showed intermediate values between inter-intraspecies diversity usually reported for Passerines. We estimated a divergence time at ca. 890 kya (554–1.259 kya HPD). Our findings showed a mismatch in subspecies assignment using morphology and genetic information and a marked differentiation between the eastern L. s. niloticus and all other L. senator populations sampled.